Identification of Student Difficulties in The Implementation of Basic Physics Lecture - Muhammad Zuhdi; Muh. Makhrus; Ahmad Busyairi; Wahyudi Wahyudi (Jurnal Penelitian Pendidikan IPA, 2022)
The objective of this research is to find out the causes of low student learning outcomes in the Basic PhysicsÂ  course in the physics Education Dept. University of Mataram in 2021. This type of research is a qualitative descriptive that examines the main problems related to the difficulties of the study of physics. The research population was all students in the Physics Education Dept, University of Mataram who took the Basic Physics course. The research sample was students who took the short semester course in the Basic Physics course using the purposive sample technique. While the research instrument used is in the form of a questionnaire whose answers have been provided, so that respondents just choose the options that have been provided. The results of the analysis show that learning difficulties in studying mechanics lie in the basic mathematical abilities, namely differential and integral. Thus, teachers need to develop learning strategies so that students' thinking skills in solving problems are increasing.